2011
DOI: 10.3390/s110302447
|View full text |Cite
|
Sign up to set email alerts
|

A Non-Invasive Thermal Drift Compensation Technique Applied to a Spin-Valve Magnetoresistive Current Sensor

Abstract: A compensation method for the sensitivity drift of a magnetoresistive (MR) Wheatstone bridge current sensor is proposed. The technique was carried out by placing a ruthenium temperature sensor and the MR sensor to be compensated inside a generalized impedance converter circuit (GIC). No internal modification of the sensor bridge arms is required so that the circuit is capable of compensating practical industrial sensors. The method is based on the temperature modulation of the current supplied to the bridge, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…GMR sensors are resistive elements, so they are affected by thermal variations, quantified by the corresponding temperature coefficient ( ) [ 33 ]. It has been demonstrated that these effects can be reduced by biasing the sensors with current [ 3 ], by arranging the sensors in a bridge configuration [ 34 ] or by designing external compensation circuitry [ 35 ].…”
Section: Spreading the Performancementioning
confidence: 99%
See 1 more Smart Citation
“…GMR sensors are resistive elements, so they are affected by thermal variations, quantified by the corresponding temperature coefficient ( ) [ 33 ]. It has been demonstrated that these effects can be reduced by biasing the sensors with current [ 3 ], by arranging the sensors in a bridge configuration [ 34 ] or by designing external compensation circuitry [ 35 ].…”
Section: Spreading the Performancementioning
confidence: 99%
“…In [ 35 ], a ruthenium (Ru) meandered thermistor was deposited together with a engineered spin-valve based full bridge sensor. It was measured a of 0.11%/ C for the spin-valve resistors and 0.16%/ C for the Ru thermistor.…”
Section: Spreading the Performancementioning
confidence: 99%
“…The MTJ elements were deposited and fabricated simultaneously, and therefore have similar characteristic curves and reference layer orientations. The full bridge configuration was obtained so that the test conducting wire (U-shaped current line) mounted below the chip was aligned with each MTJ array ( Figure 1 b), to enable opposing magnetic fields in each pair of MTJ elements and opposite sensitivities to the magnetic field [ 29 ].…”
Section: Sensor Descriptionmentioning
confidence: 99%
“…A generalized impedance converter with reference input current can be utilized to perform the thermal compensation [26,27]. This compensation technique is compatible with the Wheatstone bridge circuit, and could successfully bring TMCA from −0.024%·°C −1 to −0.007%·°C −1 .…”
Section: Typical Performancementioning
confidence: 99%